Relationship Between High-Density Lipoprotein and Low-Density Lipoprotein Lipid Profiles in Patients with Type 2 Diabetes Mellitus: Hubungan Profil Lipid High-Density Lipoprotein & Low-Density Lipoprotein Pada Penderita Diabetes Melitus Tipe 2 - Noor Zahwa Mubarakah; Nurul Amelia; Rizka Ayu Wahyuni; Nurbidayah (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Type 2 Diabetes Mellitus is often accompanied by lipid metabolism disorders that may increase the risk of cardiovascular complications. This study aimed to determine the relationship between glucose levels and High-Density Lipoprotein (HDL) and Low-Density Lipoprotein (LDL) levels in patients with Type 2 Diabetes Mellitus. This study used a cross-sectional design with a descriptive-analytic approach. The study was conducted at the Clinical Pathology Laboratory of RSDI Banjarbaru in July 2025 using secondary data from the medical records of 45 patients with Type 2 Diabetes Mellitus selected through purposive sampling. Data were analyzed using the Chi-Square test and Fisher’s Exact Test. The results showed that most respondents had high glucose levels with normal HDL levels in 33 patients (73.3%) and high LDL levels in 41 patients (91.1%). Statistical analysis showed no significant relationship between glucose levels and either HDL or LDL levels (p > 0.05). It can be concluded that glucose levels were not significantly associated with HDL and LDL levels in patients with Type 2 Diabetes Mellitus.